2022
DOI: 10.3389/fmars.2022.1082337
|View full text |Cite
|
Sign up to set email alerts
|

Second-order Stokes wave-induced dynamic response and instantaneous liquefaction in a transversely isotropic and multilayered poroelastic seabed

Abstract: The ocean waves exhibit obvious non-linearity with asymmetric distribution of wave crests and troughs, which could induce significantly different effect on the seabed compared to the commonly used linear wave theory. In this paper, a semi-analytical solution for a transversely isotropic and multilayered poroelastic seabed under non-linear ocean wave is proposed by virtue of the dual variable and position (DVP) method. The ocean wave and seabed are, respectively, modelled using second-order Stokes theory and Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…On the basis of the dynamic stiffness matrix, Chen et al [19] considered the combined load of current and wave to propose a semi-analytical solution for the dynamic response of multilayered transversely isotropic seabed and found an underestimated maximum liquefaction depth under the isotropic assumption. Zhang et al [20] also proposed a semi-analytical solution using fully dynamic Biot's theory and second-order Stokes theory and found that the stratification can greatly impact the seabed response caused by waves and that it is easy to liquefy when the surface layer is hard. Qin et al [21] studied the seabed response around a dumbbell-shaped cofferdam under wave action using a three-dimensional numerical model built by OpenFOAM and found that the maximum liquefaction depth around the cofferdam occurred near the steel casing along the centerline of the cofferdam.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the dynamic stiffness matrix, Chen et al [19] considered the combined load of current and wave to propose a semi-analytical solution for the dynamic response of multilayered transversely isotropic seabed and found an underestimated maximum liquefaction depth under the isotropic assumption. Zhang et al [20] also proposed a semi-analytical solution using fully dynamic Biot's theory and second-order Stokes theory and found that the stratification can greatly impact the seabed response caused by waves and that it is easy to liquefy when the surface layer is hard. Qin et al [21] studied the seabed response around a dumbbell-shaped cofferdam under wave action using a three-dimensional numerical model built by OpenFOAM and found that the maximum liquefaction depth around the cofferdam occurred near the steel casing along the centerline of the cofferdam.…”
Section: Introductionmentioning
confidence: 99%